Using ginseng for menopausal women's health care: A systematic review of randomized placebo-controlled trials. (August 2022) - Lee, Hye Won; Ang, Lin; Lee, Myeong Soo
Abstract: Purpose: This systematic review aimed to update the evidence of ginseng on menopausal women's health care. Methods: We searched six databases (PubMed, AMED, EMBASE, the Cochrane Library, RISS, and KoreaMed) from their inception to April 2022 and included all placebo-controlled RCTs comparing any type of ginseng in menopausal women. The methodological quality of all studies was assessed using the Cochrane Risk of Bias Tool 2.0. Results: We included 15 RCTs with our inclusion criteria. The majority of studies considered bias a concern. Ginseng reduced menopausal symptoms in three studies (n = 515; standardized mean difference (SMD): −0.40, 95% confidence interval (CI): −0.73 to −0.07, P = 0.02) and lowed hot flashes (n = 515; SMD: −0.34, 95% CI: −0.66 to −0.01, P = 0.04). The meta-analysis of three other studies failed to show that ginseng was beneficial for sexual function (n = 491; SMD: 0.31, 95% CI: −0.30 to 0.92, P = 0.32). Three RCTs showed positive effects of ginseng on the quality of life score (n = 515, SMD: −0.31, 95% CI: −0.61 to −0.01, P = 0.05). In two studies, ginseng failed to produce significant effects on the vaginal maturation index and vaginal pH. Another three RCTs failed to demonstrate a beneficial effect of Korean red ginseng (KRG) on endometrial thickness. Conclusion: This study demonstrated that ginseng can significantly reduce hot flashes, menopausal symptoms, and quality of life in menopausal women. In contrast, neither KRG nor ginseng appeared to have any direct effect on sexual dysfunction, hormones or biomarkers, or endometrial thickness. More rigorous RCTs are needed to overcome the current limitations. Highlights: Several individual herbs, including fennel and ginseng, are also commonly used to treat menopausal symptoms. Our study demonstrated that ginseng may significantly improve hot flashes, menopausal symptoms, and QoL in menopausal women. More rigorous RCTs are needed to overcome the current limitations of the evidence.